Identifying and assessing assisted colonisation sites for a frog species threatened by chytrid fungus. (3rd June 2022) - Scheele, Ben C.; Brawata, Renee L.; Hoffmann, Emily P.; Loneragan, Rachael; May, Sarah; Pierson, Jennifer; Sopniewski, Jarrod D.; von Takach, Brenton
Summary: The intentional movement of species outside their indigenous range – assisted colonisation – is an emerging tool in conservation. Here, we outline the process developed to identify and assess candidate sites for assisted colonisation of the critically endangered Northern Corroboree Frog ( Pseudophryne pengilleyi ), a range‐restricted species highly threatened by chytrid fungus. We first investigated the mechanisms associated with the persistence of Northern Corroboree Frog populations with chytrid fungus and then used a combination of desktop and field surveys to identify and assess sites based on habitat suitability, capacity to allow coexistence with chytrid fungus and hydrological properties. Candidate sites were further assessed by comparing environmental and climatic conditions to historical and persisting sites. Together, these methods allowed us to identify a site that appears to be highly suitable for the species. The process outlined here provides a template for assessing assisted colonisation sites for species where ongoing threats rule out recipient sites within their indigenous range.